2007
DOI: 10.1002/jmri.20900
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of iliac and proximal femoral artery hemodynamics using time‐resolved 3D phase contrast MRI at 3T

Abstract: Purpose:To demonstrate the feasibility of time-resolved 3D MR velocity mapping at 3 Tesla for the visualization of vascular hemodynamics in normal iliac and femoral arteries. Materials and Methods:Electrocardiographically (ECG) synchronized three-dimensional (3D) CINE phase-contrast MRI with three-directional flow encoding was adapted to analyze flow in peripheral arteries at 3T. Visualization of peripheral arterial hemodynamics within the acquired data volume included 3D streamlines and time-resolved 3D parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 24 publications
1
34
0
1
Order By: Relevance
“…Several studies have demonstrated that velocity mapping is a reliable tool for detailed analysis of normal as well as abnormal blood flow features within several vessels [19][20][21][22][23]. Investigation of CSF flow in the cerebral ventricular system, however, using time-resolved 3D MR velocity mapping, has yet been performed on healthy volunteers only [24].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that velocity mapping is a reliable tool for detailed analysis of normal as well as abnormal blood flow features within several vessels [19][20][21][22][23]. Investigation of CSF flow in the cerebral ventricular system, however, using time-resolved 3D MR velocity mapping, has yet been performed on healthy volunteers only [24].…”
Section: Introductionmentioning
confidence: 99%
“…While Bilecin et al suggest subsystolic cuff compression in order to hamper the contrast agent backflow and lengthen the period of selective arterial contrast-enhancement, we sought to record the natural contrast agent dynamics by employing an ultrarapid time-resolved spoiled 3D gradient echo sequence featuring parallel imaging and echo sharing [4,5]. This technique aims to accelerate image acquisition as much as possible and has been successfully applied in several vascular territories [9][10][11][12][13]. Since data undersampling is the basic clue, we applied parallel imaging with GRAPPA (generalised autocalibrating partially parallel acquisition) and thereby obtained a 3.2 fold acceleration [6].…”
Section: Discussionmentioning
confidence: 99%
“…(1), (2) [10,14,20]. Orthogonal views of a helically sinuous tube part and a stenotic part are shown in Fig.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Swirling or helical flow is frequently observed in the coronary artery as well as several sites of the vascular system [1][2][3][4]. The aortic valve can induce swirling flow with vortex motions in the coronary artery, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%